Web 2.0 for Knowledge Management in Organizations and Their Effects on Tacit Knowledge Sharing and Perceived Learning - Anupam Kumar Nath (STIE Malangkucecwara, 2015)
Web 2.0 is a set of Internet-based applications that harness network effects by facilitating collaborative and participative computing. In this research we study the relationship between the use of Web 2.0 in KM and its effect on the tacit knowledge sharing and perceived learning. We also study the effects of KM context variables on these relationships. Our findings shows that use of Web 2.0 for KM can positively affect tacit knowledge sharing and perceived learning.